Tertullian, Apostolicity, and the Apostles - Dunn, Geoffrey David (Vox Patrum, 2024)
How did Tertullian regard the apostles? This article investigates the references to them scattered through his writings both as individuals and as a collective. It reveals that individually the apostles were remote figures who appear in the pages of the New Testament simply as interlocutors of Jesus. Even Peter, significant as he was, was someone whose role was personal to himself and not a pattern for future leadership. Yet collectively the apostles performed an important function in Tertullian’s ecclesiology; they were the first receivers and transmitters of the regula fidei, and their fidelity to that responsibility distinguished authentic Christian communities from heretical associations. The regula fidei was important to Tertullian. As a synthesis of the essentials of faith as preached and lived by Jesus, it provided the measure against which passages of Scripture and Christian belief and practice were to be interpreted. The regula relied upon the accurate and complete transmission of the message of Jesus via the apostles to the church and its leaders. The apostolicity of the church is at the heart of why Tradition is central to Christian theology.